Pemberdayaan Masyarakat melalui Sosialisasi Pembuatan Hand Sanitizer bagi DWP UIN Randen Mas Said Surakarta - Taufik, Moh; Astuti, Septin Puji; Kusumawardani, Rizky (LPkM Universitas Bakrie, 2023)
Worldwide Covid-19 pandemic leads people live in healthy life to avoid this disease. Wash hand using clean water and hand soap or hand sanitizer is one of the forms of reducing the possibility to suffer from Covid-19. The making of hand sanitizer is essential to be introduced to the society through community engagement activities. This activity aims to improve the skill of the audience to produce alcohol based-hand sanitizer. Along with Dharma Wanita Persatuan (DWP) UIN Raden Mas Said Surakarta, the Centre for Science and Technology UIN Raden Mas Said Surakarta conducted a workshop for producing alcohol based-hand sanitizer. This workshop is presented to DWP UIN Raden Mas Said members. The workshop was delivered by using an educational training lecture; lecture and training. The trainer introduced the materials and the step by step of making hand sanitizer. After the workshop, evaluation is conducted by distributing online-questionnaire to the audience. Four aspects were evaluated are material for producing hand sanitizer, tools and instruments for producing hand sanitizer, production process of the hand sanitizer, and what are the role and function of material for hand sanitizer. By using Wilcoxon sign-test, the results of the evaluation show that the audience have a significant understanding in terms of the knowledge to material and tools for producing hand sanitizer.